A cross-sectional, prospective ocular motor study in 72 patients with Niemann-Pick disease type C - Bremova-Ertl, Tatiana; Abel, Larry; Walterfang, Mark; Salsano, Ettore; Ardissone, Anna; Malinová, Věra; Kolníková, Miriam; Gascón Bayarri, Jordi; Reza Tavasoli, Ali; Reza Ashrafi, Mahmoud; Amraoui, Yasmina; Mengel, Eugen; et al. (European journal of neurology, 2021)
OBJECTIVE: To characterize ocular motor function in patients with Niemann-Pick disease type C (NPC). METHODS: In a multicontinental, cross-sectional study we characterized ocular-motor function in 72 patients from 12 countries by video-oculography. Interlinking with disease severity, we also searched for ocular motor biomarkers. Our study protocol comprised reflexive and self-paced saccades, smooth pursuit, and gaze-holding in horizontal and vertical planes. Data were compared with those of 158 healthy controls (HC). RESULTS: Some 98.2% of patients generated vertical saccades below the 95% CI of the controls' peak velocity. Only 46.9% of patients had smooth pursuit gain lower than that of 95% CI of HC. The involvement in both downward and upward directions was similar (51°/s (68.9, [32.7-69.3]) downward versus 78.8°/s (65.9, [60.8-96.8]) upward). Horizontal saccadic peak velocity and latency, vertical saccadic duration and amplitude, and horizontal position smooth pursuit correlated best to disease severity. Compensating strategies such as blinks to elicit saccades, and head and upper body movements to overcome the gaze palsy, were observed. Vertical reflexive saccades were more impaired and slower than self-paced ones. Gaze-holding was normal. Ocular-motor performance depended on the age of onset and disease duration. CONCLUSIONS: This is the largest cohort of NPC patients investigated for ocular-motor function. Vertical supranuclear saccade palsy is the hallmark of NPC. Vertical upward and downward saccades are equally impaired. Horizontal saccadic peak velocity and latency, vertical saccadic duration and amplitude, and horizontal position smooth pursuit can be used as surrogate parameters for clinical trials. Compensating strategies can contribute to establishing a diagnosis.
Keywords: pohyby očí; Saccades; Cross-Sectional Studies; Niemann-Pick Disease, Type C; lidé; Niemann-Pick type C; sakadické oční pohyby; průřezové studie; Prospective Studies; supranuclear vertical saccade palsy; supranuclear vertical gaze palsy; saccades; Humans; prospektivní studie; Niemannova-Pickova nemoc typu C; video-oculography; ocular motor function; biomarkers; Eye Movements